Electrodeposition and Catalytic Performance of Hydrophobic PbO2 Electrode Modified by Surfactant OP-10. (7th December 2021) - Shen, Ying; Li, Yudong; Yao, Yingwu; Xia, Yun; Jiao, Mengyao; Han, Enshan
Abstract : A hydrophobic PbO2 electrode modified by surfactant OP-10 was prepared by electrodeposition. The electrode has good hydrophobic surface (the hydrophobic angle can reach 123°), high over point oxygen evolution (OEP) (1.60 V vs SCE), and good service life (81 h). The electrode morphology and electrodeposition mechanism study found that the addition of OP-10 can help to build a dense PbO2 electrode surface, reduce the occurrence of side reactions, and promote the positive deposition of PbO2 . As much as 30 mg l −1 of methylene blue, as the simulated pollutant, could be degraded in 80 min under conditions of 50 mA cm −2, initial pH = 7, and a concentration of supporting electrolyte of 0.15 mol l −1, which could be easily reached. Moreover, a practical dye wastewater was employed, proving the OP-10 modified PbO2 electrode is suitable for industrial applications, where the COD of dye wastewater can be reduced from 330 to 4 mg l −1 in 120 min.